2017
DOI: 10.1007/s11669-017-0532-0
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Electro-Physical Properties of Sn-3.0Ag-0.5Cu Nanocomposite Solder Reinforced with Ni Nanoparticles in the Melting-Solidification Temperature Range

Abstract: The electrical conductivity of nanocomposite Sn-3.0Ag-0.5Cu alloys with two different weight percentages of Ni nanoparticles (1.0 and 2.0 wt.%) was measured over a wide temperature range. The samples were produced using a cold pressing method: Sn-3.0Ag-0.5Cu powder and Ni nanopowder were mechanically mixed and pressed into 8 mm diameter rods. Ni nanoparticles were synthesized via a chemical reduction method and characterized by a core/ shell structure. Temperature dependencies of the electrical conductivity re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…The transport properties of the liquid SAC305 alloys with Ni nanoparticles were investigated in Refs. [20,21]. The present research acts as a follow-up to these studies, focusing on structural investigations in liquid and after-reflow solid states.…”
Section: Introductionmentioning
confidence: 94%
“…The transport properties of the liquid SAC305 alloys with Ni nanoparticles were investigated in Refs. [20,21]. The present research acts as a follow-up to these studies, focusing on structural investigations in liquid and after-reflow solid states.…”
Section: Introductionmentioning
confidence: 94%
“…However, Al 2 O 3 nanoparticles did not participate in phase formation but acted as a grain refiner. Yakymovych et al (2017) added Ni nanoparticles into SAC using a cold-pressing method in which powders of SAC and Ni nanopowders were mixed mechanically, and processed into 8 mm diameter rods. It was observed that the presence of Ni nanoparticles in SAC formed a (Cu, Ni) 6 Sn 5 phase which participated in the refinement of the microstructure due to the fine distribution of IMCs in the Sn matrix.…”
Section: Microstructurementioning
confidence: 99%
“…Ag 3 Sn and Cu 6 Sn 5 , which stopped the growth of grains/IMCs during aging/reflowing. However, Al 2 O 3 nanoparticles did not participate in phase formation but acted as a grain refiner (Yakymovych et al, 2017). added Ni nanoparticles into SAC using a cold-pressing method in which powders of SAC and Ni nanopowders were mixed mechanically, and processed into 8 mm diameter rods.…”
mentioning
confidence: 99%
“…The reinforcement of solder is proven to enhance the quality of solder mechanically, thermally and its wetting properties depending on the reinforced materials. Research on the nano-reinforced solder became more vigorous as researchers found out that adding nanoparticles such as cobalt [1], copper [9][10][11], silver [12], nickel [13][14][15], diamond [3], the molecule of iron nickel oxide [16], iron oxide [17], titanium dioxide [18], zinc oxide [19] and others to the solder proven to increase the solder properties in terms of either one, mechanical, thermal, wetting and intermetallic compound layer or all of them. Researchers have also added rare earth elements such as Erbium (Er) [20], Cerium (Ce), and Lanthanum (La) [21], into the SAC solder.…”
Section: Introductionmentioning
confidence: 99%